Alex. L. du Toit (1878-1948): semblanzas de su vida y de su aporte al conocimiento de la geología sudamericana - Cingolani, Carlos Alberto (2008)
This contribution deals on a biographical sketch of the main activity developed by the South African geologist Alexander Logie du Toit, who about 1920, was constituted in a geological authority in all that referred to the Gondwanan Upper Paleozoic glaciations. His geological knowledge was stimulated to work in other regions of Africa, Madagascar, India, Australia and South America. It is evident that in your interior, was installed the possibility of a union of continents as coherent explanation of many geological phenomena that he had observed. In 1923 supported by a grant of the Carnegie Institution of Washington, he travels to South America for 6 months. The field trips being employed at the Palaeozoic and Mesozoic of Argentina, Chile, Uruguay, Bolivia and Brazil. As a result of this research he published in 1927 the paper on the “Geological Comparison of South America with South Africa”, already strongly stimulated by the theory of the continental drift, defended for A. Wegener. During his trips in South America, he had contact prominent colleagues of several countries. In Buenos Aires he took contact with the Director at the time of the Geological Survey Dr. Jose María Sobral. Franco Pastor, Augusto Tapia and Juan José Nágera were designed by Sobral to accompanying him on the field trips, which had during two months visiting Córdoba, San Luis, San Juan, Mendoza and Buenos Aires provinces. Also du Toit is grateful during his visit in Argentina for the collaboration of Pablo Groeber, Roberto Beder, Juan Rassmuss, Anselmo Windhausen, Ricardo Wichmann, H. Hausen and Juan Keidel. Likewise he recognizes also the support of the Walther Schiller of the Museum of La Plata. The historical personal correspondence with relevant geologists from Argentina, especially with Horacio Harrington, is preserved at the University of Cape Town, South Africa. These historical documents, partially exposed in this article, are a clear demonstration of du Toit’s geological knowledge of several regions of our country.